Implementation of Cognitive Mapping Algorithm for Robot Navigation System - Ismail , Amelia Ritahani; Desia, Recky; Zuhri, Muhammad Fuad Reza; Daniel, Raja Muhammad (2014)
Abstract—Mobile robot is a construction of robot that is equipped with wheel to move around its environment in finishing its specific task. Robot will be given some algorithm for certain task. In this project, we are going to build the cognitive mapping algorithm that can be implemented to the mobile robot. This mobile robot will be given some inputs which are horizontal and vertical value and start and goal point and a task which is to move from start point to goal point. Some obstacles are also located in the arena and the mobile robot must be able to avoid any given obstacles to reach the goal point. After doing all implementation, finally, some comparison between robot mapping and robot edge follower will be done to observe the differences between these algorithms in term of time and path needed.